Textural and rheological characterisations of sago starch and sago starch sugar gels - Teng, Li Yuen (2011)
The behaviour of native sago starch was investigated through characterisation,rheological and textural measurements in finding its use as a gelling agent in frozenbaked products. The effects of sago starch (6-8%), sugar (25-35%), and shearing speed of mixer (20-50 rpm) on rheological and textural characteristics of gel were investigated by means of response surface methodology. Increase in sago starch and sugar levels both increased (P < 0.01) gel stiffness. Higher shearing speeds reduced (P < 0.05) gel stiffness due to a decrease in starch swelling and an increase in starch breakdown during cooking. The values of the experimental variables which minimised and maximised the textural parameters of hardness, gumminess, resilience, cohesiveness, and springiness were estimated by means of ridge analysis to determine the processing conditions at which these extremes can be reached. The maximum gel cohesiveness brought by the processing variables was set as the criterion to obtain optimum formulation and processing of sago-starch based gels. Utilising the optimised formulation and processing condition for gel setting, the pasting behaviour, rheological and textural characteristics of sago starch-sugar gels were compared with those of corn, wheat, tapioca, and potato starches. The morphological and thermal properties of these starches were investigated via scanning electron microscopy and differential scanning calorimetry respectively.High-amylose cereal starches (wheat and corn) produced harder gels (hardness = 225.1–248.0 g), while low-amylose root starch (tapioca) produced softer gels (hardness = 4.9 g). Sago and potato starches produced gels with high cohesiveness (0.90–0.94), indicating good setting of gels. The effect of freezing and thawing on rheological and textural characteristics of gels were investigated. The freezing and thawing processes greatly increased the viscoelasticity and hardness of sago starch-sugar gels. These negative effects were significantly reduced by reheating the freeze-thawed gels at high temperature (80 °C). The freeze-thaw stability of various starch gels were investigated by gravimetric measurements of the water of syneresis after three freeze-thaw cycles. Sago starch produced gels with relatively low syneresis (3.23%) compared with corn (15.5%) and wheat (4.26%) starches. The high cohesiveness and low syneresis of sago starchsugar gels, and their ability to recover from structural changes caused by freezing and thawing, implied potential use of sago starch as a gelling agent in frozen-baked products.